New species of Hexacladia Ashmead (Hymenoptera: Encyrtidae), a parasitoid of Tibraca limbativentris Stål (Hemiptera: Pentatomidae) - Keneson Klay Gonçalves Machado; Valmir Antonio Costa; John Noyes; Raimunda Nonata Santos de Lemos; Elizabeth Araújo Costa; Janaina Marques Mondego (Revista Brasileira de Entomologia, 2024)
ABSTRACT The rice stink bug, Tibraca limbativentris Stål (Hemiptera: Pentatomidae), is a significant pest of rice cultivation in Brazil and attacks plants during both vegetative and reproductive phases. Natural enemy surveys conducted in plantations located in Arari, Miranda do Norte, Matões do Norte, Santa Rita, and Viana (state of Maranhão, Brazil) led to the discovery of a new species of parasitoid, which is described in this study. Hexacladia lemosae Costa, Noyes & Machado sp. nov. (Hymenoptera: Encyrtidae) is the first species of its genus associated with T. limbativentris and develops as a gregarious endoparasitoid in adult stink bugs, occasionally in nymphs. The parasitoid emerges from the host while host is still alive.